Digital Approaches for Myositis - Knitza, Johannes; Kuhn, Sebastian; Gupta, Latika (Current Rheumatology Reports, 2023)
Purpose of Review: This article serves as a comprehensive review, focusing on digital approaches utilized in the diagnosis, monitoring, and treatment of patients with idiopathic inflammatory myopathies (IIM). The authors critically assess the literature published in the last three years, evaluating the advancements and progress achieved in this specific domain. Recent Findings: Remarkable strides have been made in the realm of digital diagnostic support, particularly in image analysis and clinical prediction models, showing promise in aiding the diagnosis of IIM. The field of remote patient monitoring has also witnessed significant advancements, revolutionizing the care process by offering more convenient, data-driven, and continuous monitoring for IIM patients. Various digital tools, such as wearables, video- and voice consultations, and electronic patient-reported outcomes, have been extensively explored and implemented to enhance patient care. Survey studies consistently reveal a high acceptance of telehealth services among patients. Additionally, internet-based studies have facilitated the efficient and rapid recruitment of IIM patients for research purposes. Moreover, the integration of sensors and exoskeletons has shown great potential in significantly improving the functionality and quality of life for individuals with muscle weakness caused by IIM. Summary: The integration of digital health solutions in the care of IIM patients is steadily gaining attention and exploration. Although the existing evidence is limited, it does indicate that patients can be adequately and safely supported through digital means throughout their entire healthcare journey. The growing interest in digital health technologies holds the promise of improving the overall management and outcomes for individuals with idiopathic inflammatory myopathies.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Digital; eHealth; Myositis; Telehealth; Wearables